Analysis of prevalence and clinical features of multicystic ameloblastoma and its histological subtypes in South Indian sample population: A retrospective study over 13 years - Manickam Selvamani; Andamuthu Yamunadevi; Praveen S Basandi; G S Madhushankari (Wolters Kluwer Medknow Publications, 2014)
Objective: The study was designed to analyze the frequency and clinical features of multicystic ameloblastoma and its histological variants in South Indian sample population, as there is minute information available in the English literature. Methodology: The study source was the biopsy specimens retrieved from the archives of the Department of Oral and Maxillofacial Pathology, College of Dental Sciences, Davangere, Karnataka, India, during the past 13 years, from 2001 to 2013. Clinical data for the study were obtained from the case records of patients and the analyzed clinical variables were age, gender and anatomical location. Histologically, hematoxylin and eosin stained sections fitting the World Health Organization (2005) criteria for diagnosis of multicystic ameloblastoma were selectively included. Results: Of the 3026 biopsy reports analyzed, 103 cases were odontogenic tumors (3.4%) and 58 cases were ameloblastoma. 31 cases of multicystic ameloblastoma, including follicular ameloblastoma (54.8%), acanthomatous ameloblastoma (29%), plexiform ameloblastoma (6.5%), granular cell ameloblastoma (6.5%) and desmoplastic ameloblastoma (3.2%) were recorded. The age of the patients during the presentation of the lesion was ranging from 21 to 73 years, with a mean of 39.5 years. The most frequent clinical manifestation was swelling, followed by a combination of pain and swelling. In our study, ameloblastoma showed distinct anatomic predilections for occurrence in mandible (96.8%) rather than maxilla (3.2%). This study result also indicated that there is geographical variation in the frequency and distribution of ameloblastoma.